PENGARUH PERMAINAN TRADISIONAL GALAH ASIN TERHADAP KEMAMPUAN MOTORIK KASAR ANAK DI TAMAN KANAK-KANAK YAYASAN AMALAN KOTA PADANG - Julianti, Dora; Nurhafizah; Suryana, Dadan; Syafnita, Tisna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low gross motor skills observed among early childhood students at the Yayasan Amalan Kindergarten in Padang City. Issues included poor balance during jumping and a lack of agility, attributed to limited outdoor physical activity variations and high daily screen time (mobile phone usage). Consequently, this study aimed to determine the impact of the traditional game galah asin on children's gross motor skills. A quantitative experimental method was employed using a quasi-experimental design with pre-tests and post-tests administered to both experimental and control groups. The study population consisted of 30 students from Yayasan Amalan Kindergarten, divided into three classes: Ali, Umar, and Uthman. The Umar class (10 children) was designated as the experimental group, while the Ali class (10 children) served as the control group. The results revealed a highly significant difference in gross motor skill development between the two groups. In the control group, the overall score showed only a modest increase, rising from a pre-test total of 162 (mean: 16.2) to a post-test total of 185 (mean: 18.5). In contrast, the experimental group experienced a much more substantial developmental surge, with scores rising from a pre-test total of 156 (mean: 15.6) to a post-test total of 229 (mean: 22.9). Analysis of the pre-test and post-test data yielded an average gain score of 7.3 for the experimental group and 2.3 for the control group. Thus, it can be concluded that the traditional game *galah asin* is highly effective and is recommended as a fun, active learning tool to stimulate gross motor skills among children at Yayasan Amalan Kindergarten in Padang City.